2015
DOI: 10.1002/ece3.1564
|View full text |Cite
|
Sign up to set email alerts
|

Consumer trait variation influences tritrophic interactions in salt marsh communities

Abstract: The importance of intraspecific variation has emerged as a key question in community ecology, helping to bridge the gap between ecology and evolution. Although much of this work has focused on plant species, recent syntheses have highlighted the prevalence and potential importance of morphological, behavioral, and life history variation within animals for ecological and evolutionary processes. Many small-bodied consumers live on the plant that they consume, often resulting in host plant-associated trait variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 82 publications
0
20
1
Order By: Relevance
“…For example, wrack perturbation represented a (weak) stress on snail density, with magnitude playing a key role in both the short-and longterm. These stress effects likely resulted from negative impacts on Spartina, which snails use as a refuge from inundation and predation, as well as for foraging (Silliman and Newell 2003, Hughes 2012, Kimbro 2012, Hughes et al 2015. In contrast, wrack represented both a stress and a subsidy for fiddler burrow density, with positive and negative effects of wrack addition depending on individual perturbation components and overall intensity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, wrack perturbation represented a (weak) stress on snail density, with magnitude playing a key role in both the short-and longterm. These stress effects likely resulted from negative impacts on Spartina, which snails use as a refuge from inundation and predation, as well as for foraging (Silliman and Newell 2003, Hughes 2012, Kimbro 2012, Hughes et al 2015. In contrast, wrack represented both a stress and a subsidy for fiddler burrow density, with positive and negative effects of wrack addition depending on individual perturbation components and overall intensity.…”
Section: Discussionmentioning
confidence: 99%
“…While it is still unclear whether Littoraria directly consumes Juncus , previous studies have illustrated a negative impact of Littoraria on Juncus biomass (Hughes et al . ). Moreover, prior work in this system has found that Spartina growing in the presence of Juncus loses less biomass to Littoraria grazing than when growing by itself (i.e., an associational refuge), most likely because Littoraria uses taller and more rigid Juncus stems as a refuge from predation (Hughes ).…”
Section: Methodsmentioning
confidence: 97%
“…ITV combines genetic diversity and phenotypic plasticity, and is assumed to play a major role in community assembly processes (Violle et al, ). For instance, ITV can mediate species coexistence (Turcotte & Levine, ), determine the ability of natural systems to cope with environmental changes (González‐Suárez & Revilla, ; Jung et al, ; Laurila, Karttunen, & Merilä, ), and control competitive or trophic interactions (Hughes, Hanley, Orozco, & Zerebecki, ; Le Bagousse‐Pinguet et al, ; Zhao, Villéger, Lek, & Cucherousset, ).…”
Section: Introductionmentioning
confidence: 99%